Temperature characterization of an operando flow reactor for heterogeneous catalysis. (7th June 2019) - Pfaff, Sebastian; Karlsson, Hanna; Nada, Fahed Abou; Lundgren, Edvin; Zetterberg, Johan
Abstract: In this work, we present several methods to determine the temperature of a catalyst sample, as well as the gas surrounding it, in a typical flow reactor used for operando research on heterogeneous catalysis. To determine the sample temperature, we present an approach using calibrated IR-camera imagery, as well as thermographic phosphors. For the gas temperature, we present methods to extract temperature information from planar laser induced fluorescence measurements, one of which can be used during operando studies with an active catalyst in place.